(untitled) (Konferensiyalar | Conferences, 2024)
This article explores the linguistic richness of Khorezmian dialects, focusing on the distinct variations within the Kipchak and Oghuz dialect groups. Through a comprehensive analysis of phonetic, morphological, and lexical features, it illuminates the intricate interplay between language, culture, and history in the Khorezm region. Drawing from historical, archaeological, and ethnographic research, the study sheds light on the unique identity markers and cultural heritage embedded within these dialects. By examining the nuances of Kipchak and Oghuz variations, this research contributes to a deeper understanding of Khorezm’s diverse linguistic landscape and underscores the importance of preserving its rich heritage for future generations.